Analisis rasio solvabilitas untuk menilai kinerja keuangan terhadap aset dan equity pada PT. Telkom Indonesia (PERSERO) tbk. Periode 2019-2023 - Ash Shiddiqi, M. Zidan Fahmi (Maliki Interdisciplinary Journal, 2025)
This study aims to evaluate the solvency ratio as a key indicator of financial performance for PT Telkom Indonesia (Persero) Tbk. during the period of 2019 to 2023. The ratios analyzed include the Debt to Equity Ratio (DER), Debt to Asset Ratio (DAR), and Long Term Debt to Equity Ratio (LTDER). The researcher employed a quantitative descriptive analysis method, utilizing data derived from the company's financial statements. The findings indicated that while the DER exhibited fluctuations, it consistently remained within acceptable limits. Furthermore, both the DAR and LTDER demonstrated robust performance, characterized by relatively low levels of debt in relation to equity and total assets. This research offers insights into the financial standing of the company and provides recommendations for future enhancements. Additionally, it is anticipated that this study will contribute to the advancement of theory and practice in corporate financial management, as well as furnish valuable information for stakeholders, including investors, management, and regulatory bodies.